Pemberdayaan Masyarakat melalui Inovasi Sabun Cuci Piring dan Edukasi Menabung di Desa Sidomukti Baru - Yeni Yolanda Simatupang; Cindy Aulia Zalyanti; Keisya Putri Balqis; Kusmilawaty Kusmilawaty; Nuraila Rachman (Pusat Riset dan Inovasi Nasional, 2026)
The Community Service Program (KKN) in Sidomukti Baru Village aims to enhance the community’s productive skills and financial awareness through training on dishwashing soap innovation and saving education. The main problems faced by the local community are the lack of skills in creating economically valuable products and low awareness of household financial management. This activity employed a descriptive qualitative method with a participatory approach, where the community was actively involved in all stages of implementation, from planning and execution to evaluation. The results show that the dishwashing soap training effectively improved participants’ skills and creativity in processing simple materials into marketable products with local economic potential. Meanwhile, the saving education activities successfully increased financial literacy and encouraged wise financial behavior within families. Through active community participation, this program not only provided new skills but also fostered economic independence and strengthened the spirit of cooperation as a foundation for sustainable empowerment at the village level.